Pendampingan Calon Konselor dalam Mereduksi Kecemasan pada Anak Korban Kekerasan Seksual di Pusat Pelayanan Terpadu (PPT) Jawa Timur Tahun 2018 - Amriana, Amriana; Munir, Misbahul (Proceedings of Annual Conference on Community Engagement, 2018)
The assistance program of prospective counselor was focused on the students of Islamic Guidance and Counseling Program in handling the victims of sexual violence at the Pusat Pelayanan Terpadu (PPT) in East Java. The objectives in this activity are: 1) To provide insight about assisted locations in the Pusat Pelayanan Terpadu (PPT) in East Java, 2) Provide understanding the process and developing counseling programs, 3) Provide understanding about the stages of intervention in counseling, 4). Provide understanding about the evaluation and follow-up to the counseling program. This assistance uses the Service Learning approach. Service Learning approach is a program that integrates learning and service. The target of this assistance is students of Islamic Guidance and Counseling Program who will conduct practice or apprenticeship in the Pusat Pelayanan Terpadu (PPT) in East Java, as many as 7 people. Implementation of this assistance is in the span of 3 months, namely in March-May 2018 and carried out at Pusat Pelayanan Terpadu (PPT) of East Java.